Optimizing antibiotic prescribing for acutely ill children in primary care (ERNIE2 study protocol, part B): a cluster randomized, factorial controlled trial evaluating the effect of a point-of-care C-reactive protein test and a brief intervention combined with written safety net advice - Lemiengre, M; Verbakel, J; De Burghgraeve, T; Aertgeerts, B; De Baets, F; Buntinx, F; De Sutter, A (BioMed Central, 2014)
Background: Despite huge public campaigns, there is still overconsumption of antibiotics in children with self-limiting diseases. Possible explanations may be the physicians’ and parents’ uncertainty about the gravity of the disease and inadequate communication between physicians and parents leading to lack of reassurance for the parents. In this paper we describe the design and methods of a trial aiming to rationalize antibiotic prescribing by decreasing this uncertainty and parental anxiety. Methods/Design: Acutely ill children without suspected serious disease consulting their family physician will be consecutively included in a four-armed cluster randomized factorial controlled trial. The intervention will consist a Point-of-Care C-reactive protein test and/or a brief intervention with safety net advice. The control group will receive usual care. We intend to include 2560 patients in 88 family practices. Patients will be followed up until cure. The primary outcome measure is the immediate antibiotic prescribing rate. Secondary outcomes are: comparison between groups of speed of clinical recovery, parental concern, parental perception of the quality of the communication, parental satisfaction, use of medication, use of diagnostic tests and medical services during the illness episode, and cost-effectiveness of the interventions. Besides this, we will observationally analyse data of the children included in the large ERNIE2-trial, but excluded in the cluster randomized trial, namely children suspected of serious disease presenting in primary care and children who initially present at the out-patient paediatric clinic or emergency department. We will search for predictors of antibiotic prescribing, speed of clinical recovery, parental concern, parental perception of communication, parental satisfaction, use of medication, diagnostic tests and medical services. Discussion: This is a unique multifaceted intervention, in that it targets both physicians and parents by aiming specifically at their uncertainty and concerns during the consultation. Both interventions are easy to implement without special training. When proven effective, they could offer a feasible way to decrease inappropriate antibiotic prescribing for children in family practice and thus avoid emergence of bacterial resistance, side effects and unnecessary healthcare costs. Moreover, the observational part of the study will increase our insight in the course, management and parent’s concern of acute illness in children. Trial registration: ClinicalTrials.gov Identifier: NCT02024282.